Juridical Analysis of The Authority of The Honorary Assembly of The Constitutional Court Against Alleged Violations of The Code of Ethics - Faturahman, Muhammad (Jurnal Indonesia Sosial Sains, 2025)
This paper is entitled "Juridical Analysis of the Authority of the Honorary Assembly of the Constitutional Court on Allegations of Violations of the Code of Ethics (In MKMK Decision Number: 5/MKMK/L/11/2023)." The main focus of this paper is to examine the violation of the code of ethics of Constitutional Court judges in the case testing process, as well as to analyze the impact of these decisions on the integrity of the institution. This research was conducted with a normative juridical approach, which relies on secondary data in the form of laws and regulations, legal doctrines, and related court decisions. The results of the study show that there is a violation of fundamental principles such as independence, impartiality, and integrity by the judge in the case under review. These violations have a serious impact on the credibility of the Constitutional Court, raise public doubts about the neutrality of the institution, and set a bad precedent for the Indonesian legal system. In addition, weaknesses in the supervision mechanism and the application of the judge's code of ethics are also factors that worsen the situation. This study recommends strengthening the authority of the Constitutional Court Honorary Assembly, drafting a more specific code of ethics, and implementing stricter and more transparent supervision mechanisms. This effort is expected to increase accountability and maintain the integrity of the Constitutional Court as an institution that safeguards the rule of law.